Falls After Discharge From Hospital: Is There a Gap Between Older Peoples’ Knowledge About Falls Prevention Strategies and the Research Evidence? - Hill, A.; Hoffman, T.; Beer, C.; McPhail, S.; Hill, Keith; Oliver, D.; Brauer, S.; Haines, T. (The Gerontological Society of America, 2011)
Purpose: The aim of this study was to examine whether older people are prepared to engage in appropriate falls prevention strategies after discharge from hospital. Design and Methods: We used a semi-structured interview to survey older patients about to be discharged from hospital and examined their knowledge regarding falls prevention strategies to utilize in the post-discharge period. The study was part of a prospective cohort study, nested within a larger, randomized controlled trial. Participants (n = 333) were asked to suggest strategies to reduce their falls risk at home after discharge, and their responses were compared with current reported research evidence for falls prevention interventions. Results: Participants’ strategies (n = 629) were classified into 7 categories: behavioral, support while mobilizing, approach to movement, physical environment, visual, medical, and activities or exercise. Although exercise has been identified as an effective falls risk reduction strategy, only 2.9% of participants suggested engaging in exercises. Falls prevention was most often conceptualized by participants as requiring 1 (35.4%) or 2 (40.8%) strategies for avoiding an accidental event, rather than engaging in sustained multiple risk reduction behaviors. Implications: Results demonstrate that older patients have low levels of knowledge about appropriate falls prevention strategies that could be used after discharge in spite of their increased falls risk during this period. Findings suggest that health care workers should design and deliver falls prevention education programs specifically targeted to older people who are to be discharged from hospital.